1997
DOI: 10.1677/jme.0.0190163
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear orphan receptors COUP-TFII and Ear-2 act as silencers of the human oxytocin gene promoter

Abstract: We have previously shown that COUP-TFII and Ear-2, two members of the nuclear orphan receptor family, are able to repress oestrogen-stimulated transcriptional activity of the human oxytocin (OT) gene promoter by binding to a site that overlaps with the oestrogen response element (ERE) present in the 5 flanking region of the gene. Although most nuclear receptor-mediated transcriptional repression conforms with the paradigm of passive repression and involves competitive binding to an activator site, active repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 33 publications
(29 reference statements)
1
18
0
Order By: Relevance
“…COUP-TFII expression during embryonic development is significant for the development of forebrain and several other brain regions including amygdala [4850]. It has been shown that COUP-TFII can also act as a silencer of the human oxytocin gene promoter in vitro [51]. COUP-TFII is an interesting candidate gene and its role in regulation of behavior in foxes will be further evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…COUP-TFII expression during embryonic development is significant for the development of forebrain and several other brain regions including amygdala [4850]. It has been shown that COUP-TFII can also act as a silencer of the human oxytocin gene promoter in vitro [51]. COUP-TFII is an interesting candidate gene and its role in regulation of behavior in foxes will be further evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Ear-2 binds to a site that overlaps the estrogen response element on the promoter region of the oxytocin gene (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…IFI16 protein is involved in the control of cell cycle regulation via modulation of TP53 (p53) and its target gene regulation (Kwak et al 2003). For NR2F2 (COUP-TFII), a nuclear orphan receptor, active repression of the human oxytocin gene promoter was shown in the uterine epithelial cells (Chu & Zingg 1997). In the mouse, NR2F2 haploinsufficiency results in decreased progesterone synthesis in the corpus luteum leading to reduced ability of the endometrium to support pregnancy (Takamoto et al 2005).…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%